SOME QUESTIONS OF A STATE AND LEGAL REGULATION OF WATER RESOURCES IN KAZAKHSTAN - Nurzat Shairbekkyzy, Шеримова (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article some questions of water resources in Kazakhstan are considered.